A Bibliometric Mapping of Islamic Work Ethics Literature: Trends, Research Clusters, and Future Implication for Muslim Librarians - Afrina, Cut; Masruri, Anis; Kusumaputri, Erika Setyanti (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: Research into Islamic Work Ethics (IWE) has predominantly focused on the corporate and banking sectors, leaving a critical gap in the library profession. This oversight limits the ability of Muslim librarians to address unique ethical challenges within the digital-era information landscape. Purpose: This study utilizes bibliometric analysis to map the intellectual structure of IWE literature, identify existing research voids, and formulate a strategic agenda for developing a value-based professional culture specifically for Muslim librarianship. Methods: The researchers conducted a bibliometric analysis of 496 Scopus-indexed documents published between 2015 and 2024. Using Biblioshiny and VOSviewer, the study mapped publication trends, global collaboration networks, and thematic clusters to evaluate the current trajectory of IWE scholarship. Findings: The study indicates significant growth in IWE literature over the last decade, with major contributions originating from Indonesia and Malaysia. However, the library profession remains conspicuously understudied. Notably, the analysis confirms that core Islamic values: sidiq (honesty), amanah (trustworthiness), fathonah (wisdom), and tabligh (communication) are formally absent from current librarianship policy frameworks. Originality/Value: As the first bibliometric study to contextualize IWE within Muslim librarianship, this research proposes an innovative conceptual model. This model integrates three essential dimensions: personal-spiritual, structural-organizational, and digital-informative, providing a roadmap for future ethical governance in LIS.